Asking for advice: A Review of the Special Request for ICES Advice of the years 2010 to 2020 - Sarfowaa, Adwoa (UiT The Arctic University of Norway, 2021)
The International Council for the Exploration of the Sea (ICES) is the primary advisory body in the North-East Atlantic, coordinating about 700 marine institutions throughout Europe, five affiliates, and other international projects. ICES offers guidance on a wide range of topics, from the impact of pollutants on individual animals to the state of fish populations and the consequences of numerous human stressors and climate on an ecoregional scale. Each year, the ICES delivers different advice to member nations on fisheries resources and ecosystems, and among the various forms of advisory service requests, the Special request system stands out. The peculiarity of the special request for ICES advice (SRIA) is reflected in a more extensive interaction between the requesters and the ICES to develop a clear and transparent advisory product in response to the request. With the advocate of ecosystem management, it is expected that a transition towards this approach is likely to increase the demand for SRIA. Dolan et al. classified the different EMs into four separate levels: SSAFM (single-species approach to fisheries management), EAFM (ecosystem approach to fisheries management), EBFM (ecosystem-based fisheries management), and EBM (ecosystem-based management). The categorization of these levels, which are here referred to as Dolan’s levels, are utilized as a tool to examine the SRIA to establish whether or not there is a trend in the EM levels. Through the research of SRIA, a novel approach for evaluating trends in single-species management to more advanced degrees of ecosystem integration may also be developed. In addition, the study set out to establish a preliminary method for studying the SRIA’s conspicuous features, see how fisheries management has been categorized toward Dolan’s levels in the SRIA, and investigate the various SRIA requesters and geographic affiliations. This research employs some elements of the Preferred Reporting Item for Systematic Reviews and Mata-Analyses (PRISMA) checklist to establish a ...